2002
DOI: 10.1164/rccm.2105090
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Breathing Reserve Index at the Lactate Threshold Is a Predictor of Mortality in Patients with Cystic Fibrosis Awaiting Lung Transplantation

Abstract: The proportion of cystic fibrosis (CF) patients dying while on the lung transplant wait list remains high; identification of such patients remains difficult. The breathing reserve index (BRI = minute ventilation/maximal voluntary ventilation) at the lactate threshold (LT) is a predictor of a pulmonary mechanical limit to incremental exercise. We hypothesized that an elevated BRI at the LT in patients with CF awaiting lung transplantation would be a predictor of wait list mortality. Forty-five consecutive patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…However, other authors have found no correlation between distance covered in a 12-MWT and survival [202]. Other authors reported that an elevated breathing reserve at hL (defined as V9E at hL divided by the MVV) is associated with an increased risk of death in CF patients awaiting lung transplantation [218]. The utility of this breathing reserve index rests on the fact that it combines a resting measure of lung function with a measure of exercise capacity that does not depend on patients attaining the point of symptom limitation.…”
Section: V9o 2 Peak and Ventilatory Indicesmentioning
confidence: 99%
“…However, other authors have found no correlation between distance covered in a 12-MWT and survival [202]. Other authors reported that an elevated breathing reserve at hL (defined as V9E at hL divided by the MVV) is associated with an increased risk of death in CF patients awaiting lung transplantation [218]. The utility of this breathing reserve index rests on the fact that it combines a resting measure of lung function with a measure of exercise capacity that does not depend on patients attaining the point of symptom limitation.…”
Section: V9o 2 Peak and Ventilatory Indicesmentioning
confidence: 99%
“…More recently, Tantisira et al [142] evaluated an index that combines the resting lung function (MVV) and ventilation at AT (an independent parameter of a patient’s ability to perform at maximal effort). They found that CF patients with a higher breathing reserve at AT (defined as Vâ€Č E at AT/MVV) had an increased mortality rate.…”
Section: Exercise Intolerance In Cystic Fibrosismentioning
confidence: 99%
“…Often, a patient's aerobic exercise capacity is also determined to make training recommendations or to determine the effects of a conditioning program [3,4,5,6]. Furthermore, exercise capacity provides prognostic information for clinical outcome and with respect to mortality [7,8,9,10,11,12,13] and may be useful for the assessment of lung transplant candidates [14,15], even though the evidence for an additional value in this respect is currently limited. Finally, exercise capacity is related to quality of life [16].…”
Section: Introductionmentioning
confidence: 99%